The Effect Stubble Cutting Height on the Vegetative and Reproductive Phase of Rice Ratoon in a Tidal Swamp - Evriani Mareza; Zainal Ridho Djafar; Rujito Agus Suwignyo; Andi Wijaya (Hasanuddin University, 2014)
Rice ratoon technology has a great potential to be developped in a tidal swamp because it can resolve various obstacles such as limited of production factor and labor, the time of planting which is depends on the season. The objective of this paper is to analyse the effect of the stubble cutting height after harvesting of first crop on the vegetative and reproductive phase of ratoon rice. The rice was planted in a tidal swamp using a direct seedling system. A randomized block design with five replicates was used. The treatment was the stubble cutting height ranged from 10, 20, 30, 40 and 50 cm from the surface of the soil. The results showed that the height of stubble cutting has significant effect on the vegetative and reproductive phases of rice ratoon. The plant height, number of tillers and number of productive tillers of ratoon was lower than first crop. The flowering of rice ratoon was faster than the first crop. Stubble cutting up to 50 cm from the surface of the soil increases plant height, number of tillers and number of productive tillers and accelerate flowering of rice ratoon. It can be known the impact of the height of stubble cutting to the vegetative and reproductive phase on rice ratoon. Future studies on effect of the height of stubble cutting for rice yield prodcution should be focussed after the ripening phase.